New missing persons identification methods and paternity disputes (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
The new DNA mapping methods may have a significant impact on paternity litigation, as they would enable the judicial contestation or the judicial establishment of a parental relationship even in cases where such disputes would have been theoretically possible, but hardly workable in practice, as the trial would have been entirely based on circumstantial evidence or, at most, on inaccurate, thus more challengeable, scientific evidence. The purpose of the present contribution is to assess the width of such impact, map the possible criticalities and provide some food for thought on the possible solutions.
Keywords: DNA testing; right to personal identity; paternity disputes; evidentiary rules; proportionality and balancing